2003
DOI: 10.1289/ehp.6288
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in dust originating from a pig-fattening farm: a new source of health hazard for farmers?

Abstract: Pig-house dust originates from feed, bedding, feces, and the animals themselves. If the animals receive drugs such as antibiotics, residues of these substances may occur in manure, in the air, or on surfaces of the respective animal house. In a retrospective study, we investigated dust samples collected during two decades from the same piggery for the occurrence of various antibiotics. In 90% of these samples, we detected up to five different antibiotics, including tylosin, various tetracyclines, sulfamethazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(120 citation statements)
references
References 19 publications
2
114
0
4
Order By: Relevance
“…Tetracycline has been found in swine manure, soil fertilized with feces, sewage, sewage sludge, surface waters and even in drinking water (Domínguez et al, 2014). Different amounts of tetracycline have been determined in soil: 5 mg kg -1 (Hamscher et al, 2003) and 98.2 mg kg -1 (Chen et al, 2012). The applied doses of tetracycline are comparable to their actual/determined concentrations in the soil environment.…”
Section: Discussionmentioning
confidence: 97%
“…Tetracycline has been found in swine manure, soil fertilized with feces, sewage, sewage sludge, surface waters and even in drinking water (Domínguez et al, 2014). Different amounts of tetracycline have been determined in soil: 5 mg kg -1 (Hamscher et al, 2003) and 98.2 mg kg -1 (Chen et al, 2012). The applied doses of tetracycline are comparable to their actual/determined concentrations in the soil environment.…”
Section: Discussionmentioning
confidence: 97%
“…Δείγματα σκόνης που συλ λέχθηκαν από ένα χοιροστάσιο σε χρονικό διάστημα δυο δεκαετιών εξετάστηκαν για την παρουσία κατά λοιπων αντιβιοτικών και στο 90% των δειγμάτων ανι χνεύθηκαν τα αντιβιοτικά τυλοσίνη, τετρακυκλινες, σουλφαμεθαζινη και χλωραμφενικόλη σε συνολική ποσότητα 12,5mg/kg σκόνης. Τα αποτελέσματα αυτά αποδεικνύουν ότι η σκόνη αποτελεί μια νέα οδό εισό δου των κτηνιατρικών φαρμάκων στο περιβάλλον με δυσμενή αποτελέσματα όχι μόνο για τα ζώα της εκμε τάλλευσης, αλλά και για την υγεία των εργαζομένων στις κτηνοτροφικές μονάδες (Hamscher et al 2003).…”
Section: είσοδος και τύχη των φαρμάκων στο περιβάλλονunclassified
“…Industrialisation of animal production may lead not only to greater animal-to-animal contact, but also to increasing animal-to-human contact, particularly when production facilities border urban areas (Murphy, 1998). Furthermore, Hamscher et al (2003) demonstrated that antibiotics can also be spread to the environment by dust. Besides environmental effects, there is concern whether the widespread use of antibiotics in animals exacerbates the rising incidence in human pathogens.…”
Section: The Problemmentioning
confidence: 99%